A biodegradable nanocapsule for through-skull NIR-II fluorescence imaging/magnetic resonance imaging and selectively enhanced radio-chemotherapy for orthotopic glioma. (October 2022) - Yin, Na; Wang, Yinghui; Cao, Yue; Huang, Ying; Jin, Longhai; Zhang, Songtao; Liu, Jianhua; Zhang, Tianqi; Lv, Zhijia; Liu, Yang; Song, Shuyan; Wang, Daguang; et al.
Abstract: Treatment of glioblastoma (GBM) remains a significant challenge in clinic because of the difficulty in discriminating the tumor margins in surgical resection, and the low blood-brain barrier (BBB) permeability hindering effective treatments. Therefore, it is urgently needed to develop theranostic nanoagents for fluorescence-guided surgery (FGS) of GBM and highly efficient therapy. Here, we constructed theranostic nanocapsules (P @ GMT-R) by encapsulating Gd2 O3 :Nd 3+ nanodots, manganese dioxide (MnO2 ), and temozolomide (TMZ) into poly (lactic-co-glycolic acid) (PLGA) with surface modification of rabies virus glycoprotein (RVG29) for through-skull the near-infrared fluorescence imaging in second windows (NIR-II FI) and selectively enhanced radio-chemotherapy. RVG29 endows nanocapsules with good abilities of crossing the BBB and accumulating into deep-seated glioma. P @ GMT-R nanocapsules exhibit outstanding NIR-II fluorescence and magnetic properties, making them can be used for NIR-II FI/MRI through the intact skull and imaging-guided surgery of orthotopic glioma combining high sensitivity and spatial resolution. Meanwhile, the nanocapsules release chemotherapeutic drugs and oxygen under the stimulation of the tumor microenvironment (TME), which assisted with the radiotherapy sensitizer Gd2 O3 :Nd 3+ nanodots to realize selective therapeutic intensification at tumor sites and low side effects. Notably, P @ GMT-R nanocapsules are biodegradable that can be cleared from the body through the hepatobiliary system and kidney. P @ GMT-R nanocapsules not only have great potential for diagnosis, surgical navigation and optimizing the standard therapeutic protocols for GBM, but also their excellent biodegradability provides exciting prospects for clinical transformation. Graphical Abstract: ga1 Highlights: Efficiently penetrating the BBB and specific targeting orthotopic glioma. Achieving through-skull MRI/NIR-II FI dual-modality imaging. Selectively enhancing radio-chemotherapy in glioma rather than normal tissues. Excellent biodegradability for exciting prospects for clinical transformation.